Gut Restricted Therapeutic Approaches to Inflammatory Bowel Disease (Global Journal of Medical Research, 2021)
Inflammatory Bowel Disease (IBD), consisting of Crohn's Disease (CD) and Ulcerative Colitis (UC), is a chronic intestinal disorder that arises due to the damaged intestinal epithelium tissue, which most often leads to relapsing. Major treatment options range from dietary intervention at an early stage of the disease, to the use of steroids or anti-inflammatory drugs for most severe conditions. However, the side effects and associated comorbidities which bring disease recurrences points towards the unmet needs of the existing treatment options, which are limited to their non-holistic mechanistic functionality. Among them, many drugs work specifically by acting locally on the gut tissue, in other words at the site of the disease, both to exert maximal efficacy as well as to avoid undesired side effects. Here we have reviewed the recent interests in the gut restricted therapeutic approaches for new IBD therapies.
Keywords: IBD; UC therapies; CD therapies; gut-restricted compounds; colon-specific compounds; non-systemic compounds